2004
DOI: 10.1162/003465304774201879
|View full text |Cite
|
Sign up to set email alerts
|

Quality of the Business Environment Versus Quality of Life: Do Firms and Households Like the Same Cities?

Abstract: This paper develops a new measure of the quality of business environment that complements existing measures of the quality of life. An annual panel of these measures is constructed and analyzed for 37 cities from 1977 to 1995. Findings indicate that many cities attractive to firms are unattractive to households, and vice versa. In addition, the size of a city's workforce increases with improvements in the quality of the business environment. In contrast, cities most likely to be dominated by retirees are those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
132
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(143 citation statements)
references
References 24 publications
(21 reference statements)
11
132
0
Order By: Relevance
“…For scaling purposes in the diagonally weighted minimum distance estimation the unexplained component is combined with the average wage across all cities. This method for calculating the unexplained component of wages is similar to studies using wage and price differentials to look at differences in amenity levels (Gabriel and Rosenthal, 2004) and provides similar estimates. depicts all cities and the right panel depicts a subset with labels.…”
Section: Datamentioning
confidence: 88%
“…For scaling purposes in the diagonally weighted minimum distance estimation the unexplained component is combined with the average wage across all cities. This method for calculating the unexplained component of wages is similar to studies using wage and price differentials to look at differences in amenity levels (Gabriel and Rosenthal, 2004) and provides similar estimates. depicts all cities and the right panel depicts a subset with labels.…”
Section: Datamentioning
confidence: 88%
“…6 Our analysis also connects to a more general research strand in urban economics that examines the amenity value of cities (e.g. Albouy, 2009Albouy, , 2012Blomquist, Berger, & Hoehn, 1988;Gabriel & Rosenthal, 2004;Gyourko & Tracy, 1991;Tabuchi & Yoshida, 2000) or neighborhoods within cities (e.g. Brueckner, Thisse, & Zenou, 1999;Carlino & Coulson, 2004;Cheshire & Sheppard, 1995;Ioannides, 2003).…”
mentioning
confidence: 85%
“…Other empirical studies found that physical capital formation [37], education quality [38,39], industrial structure [40] and agglomeration [41] served as major pulling factors to attract a well-educated worker. Land price [40,42] and living costs [38,40] negatively influenced concentration on human capital in regions. Finally, skilled workers tended to reside within metropolitan areas where they consistently performed creative activities thanks to agglomeration economies [43,44].…”
Section: Literature Reviewmentioning
confidence: 99%